Essential role of Moringa-albumin (MA) formulation in the maintenance of complement regulatory proteins on erythrocyte (TER-119) cells in diabetic mouse models - Noviana Dwi Lestari; Sulistyo Mulyo Agustini; Moh Dliyauddin; Wahyu Isnia Adharini; Ruri Vivian Nilamsari; Nashi Widodo; Sri Rahayu; Muhaimin Rifa’i (Medicinski glasnik, 2024)
Aim: To evaluate the essential role of Moringa-albumin (MA) formulation in the maintenance of complement regulatory proteins through CD55 and CD59 on erythrocyte (TER-119). Methods: Strepto-zotocin (145 mg/kg) was used to induce diabetes mice. In diabetes mellitus (DM) model mice were treated with MA formulation for 14 days at a D1 - 500 mg/kg (M) + 620 mg/kg BW (A), D2 - 1000 mg/kg (M) + 420 mg/kg (A), and D3 - 1500 mg/kg (M) + 200 mg/kg (A). On the 15th day, the mice were dissected for the isolation of their bone marrow by the flushing method. The analysis flow cytometry was performed to find out the TER-119, CD55, and CD59 expressions. The data were statistically analyzed with one-way ANOVA (ρ? 0.05) and Tukey test using SPSS version 16 for Windows. Results: The effect of MA administration in D3 group have a significant effect on increasing the profile of erythrocytes (TER-119), compared to DM (ρ?0.05) group (STZ Injection-no treatment), as well as CD59 expressed by erythrocytes. MA administration in D1 group and D3 group significantly increased the profile of CD55 expressed by erythrocytes compared to DM (ρ?0.05). Conclusions: MA formulation with D3 group (1500 mg/kg (M) + 200 mg/kg (A)) was able to maintain or control complement regula-tory proteins (CD55 and CD59) on red blood cells (erythro-cytes/TER-119) in DM.
Keywords: albumin; comple-ment regulatory; diabetes mellitus; erythrocytes; Moringa oleifera